Strategic Communication and Investor Persuasion in Syndicated Capital Raising: A Qualitative Literature Review - Ria Wulandari; Ngadi Permana (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review examines the role of strategic communication and persuasive signaling in syndicated capital raising. Drawing from interdisciplinary sources in finance, economics, and organizational behavior, the review synthesizes how lead investors utilize narrative framing, information asymmetry reduction, and trust-based messaging to influence co-investor commitment. The findings reveal that persuasion in syndication is not only a matter of financial signaling but also a communicative process that shapes collective investment decisions. Furthermore, the review highlights the critical role of communication strategies in aligning investor interests, mitigating uncertainty, and facilitating decision-making under bounded rationality. Implications for investor coordination, capital structuring, and future research directions are discussed